Real-World Estimates of Adrenal Insufficiency-Related Adverse Events in Children With Congenital Adrenal Hyperplasia - GÜRAN, TÜLAY (ENDOCRINE SOC, 2021)
Background: Although congenital adrenal hyperplasia (CAH) is known to be associated with adrenal crises (AC), its association with patient- or clinician-reported sick day episodes (SDE) is less clear. Methods: Data on children with classic 21-hydroxylase deficiency CAH from 34 centers in 18 countries, of which 7 were Low or Middle Income Countries (LMIC) and 11 were High Income (HIC), were collected from the International CAH Registry and analyzed to examine the clinical factors associated with SDE and AC. Results: A total of 518 children-with a median of 11 children (range 1, 53) per center-had 5388 visits evaluated over a total of 2300 patient-years. The median number of AC and SDE per patient-year per center was 0 (0, 3) and 0.4 (0.0, 13.3), respectively. Of the 1544 SDE, an AC was reported in 62 (4%), with no fatalities. Infectious illness was the most frequent precipitating event, reported in 1105 (72%) and 29 (47%) of SDE and AC, respectively. On comparing cases from LMIC and HIC, the median SDE per patient-year was 0.75 (0, 13.3) vs 0.11 (0, 12.0) (P < 0.001), respectively, and the median AC per patient-year was 0 (0, 2.2) vs 0 (0, 3.0) (P = 0.43), respectively. Conclusions: The real-world data that are collected within the I-CAH Registry show wide variability in the reported occurrence of adrenal insufficiency-related adverse events. As these data become increasingly used as a clinical benchmark in CAH care, there is a need for further research to improve and standardize the definition of SDE.
Keywords: 21-hydroxylase deficiency; adrenal insufficiency; adrenal crisis; congenital adrenal hyperplasia; registry; CRISIS; MANAGEMENT; ADOLESCENTS; EXPERIENCE